2007
DOI: 10.1128/aac.00771-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility of Methicillin-Resistant Staphylococcus aureus and Methicillin-Susceptible Staphylococcus aureus to a New Antimicrobial, Copper Silicate

Abstract: The soluble copper silicate (CS) MIC of 100 strains of methicillin-resistant Staphylococcus aureus and 100 strains of methicillin-susceptible S. aureus (MSSA) was 175 mg Cu/liter. Bactericidal and postantibiotic effects (>1 h) were seen at 2؋ MIC and 4؋ MIC. The frequency of mutation was <10 ؊9 , and serial passage could not extend growth beyond 1.6؋ MIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…This is worrying as copper resistance mechanisms have been shown to be important for the virulence of P. aeruginosa (Schwan et al ., 2005) and M. tuberculosis (Ward et al ., 2010). In addition soluble and metallic surface copper is increasingly being used as an antibacterial (McLean et al ., 1993; Carson et al ., 2007; Ruparelia et al ., 2008; Casey et al ., 2010). There is already evidence that chromosomal encoded copper resistance mechanisms play a role in survival on metallic copper surfaces (Elguindi et al ., 2009) with possibly other novel mechanisms also playing an important role (Santo et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This is worrying as copper resistance mechanisms have been shown to be important for the virulence of P. aeruginosa (Schwan et al ., 2005) and M. tuberculosis (Ward et al ., 2010). In addition soluble and metallic surface copper is increasingly being used as an antibacterial (McLean et al ., 1993; Carson et al ., 2007; Ruparelia et al ., 2008; Casey et al ., 2010). There is already evidence that chromosomal encoded copper resistance mechanisms play a role in survival on metallic copper surfaces (Elguindi et al ., 2009) with possibly other novel mechanisms also playing an important role (Santo et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This encouraged the EPA to register nearly 300 copper surfaces as antimicrobial products for cleaning and disinfection applications. There has been a surge in patents granted on antimicrobial coatings of copper and research activities in the past 20 years. On further investigation, it has been found that copper has an excellent efficacy against a range of pathogenic microorganisms such as Gram-positive bacteria such as S. aureus , Clostridium difficile , ,, and B. subtili , Gram-negative bacteria such as E. coli , ,,, P. aeruginosa , and Legionella pneumophila , and viruses. Motivated by the superior antimicrobial properties of copper, it finds applications in numerous ways in our life right from the construction sector to the healthcare sector for preventing infections in hospitals.…”
Section: Antibacterial and Antiviral Properties Of Nanomaterialsmentioning
confidence: 99%
“…Cu and/or its compounds have been investigated for antimarine biofouling applications , as well as for their efficacy against a spectrum of pathogenic microorganisms such as Gram-positive bacteria (e.g., Staphylococcus aureus (S. aureus), Clostridium difficile (C. difficile), ,, Bacillus subtilis ), Gram-negative bacteria (e.g., Escherichia coli (E.…”
Section: Introductionmentioning
confidence: 99%